A Method to Estimate the Hydraulic Conductivity of the Ground by TRT Analysis. Issue 1 (1st August 2016) - Liuzzo Scorpo, Alberto; Nordell, Bo; Gehlin, Signhild
Abstract: The knowledge of hydraulic properties of aquifers is important in many engineering applications. Careful design of ground‐coupled heat exchangers requires that the hydraulic characteristics and thermal properties of the aquifer must be well understood. Knowledge of groundwater flow rate and aquifer thermal properties is the basis for proper design of such plants. Different methods have been developed in order to estimate hydraulic conductivity by evaluating the transport of various tracers (chemical, heat etc.); thermal response testing (TRT) is a specific type of heat tracer that allows including the hydraulic properties in an effective thermal conductivity value. Starting from these considerations, an expeditious, graphical method was proposed to estimate the hydraulic conductivity of the aquifer, using TRT data and plausible assumption. Suggested method, which is not yet verified or proven to be reliable, should be encouraging further studies and development in this direction. Abstract : Article Impact Statement : An expeditious methodology to estimate the hydraulic conductivity of the ground by TRT analysis.